Assessment of the LCPC abrasiveness test from the view of material science / Bewertung des LCPC‐Abrasivitätstests aus werkstofftechnischer Sicht. Issue 3 (June 2015) - Küpferle, Jakob; Röttger, Arne; Alber, Michael; Theisen, Werner
Abstract The abrasiveness of crushed rock is determined in the design phase of a tunnelling project to estimate the wear on excavation and boring tools, using for example the LCPC abrasiveness test. Considered from the point of view of material science, there are problems with the validity of such an index value since important tribological factors, like for example the internal structure of the sample impeller (size, phase composition) are not considered in the current testing standard (AFNOR P18‐579). In this investigation, LCPC tests were performed with impellers of various steels of the same and different hardnesses against two abrasives (Mohs hardness 7, 9) in order to determine the influence of the internal structure and the associated tribo‐mechanical properties on the LCPC index value (ABR). In addition to the material hardness required by the standard (60 to 75 HRB ≈ 105 to 140 HV 10 according to DIN EN ISO 18265‐2013), sample materials with higher hardness values were also used in order to extend the basis of the LCPC abrasiveness index to these practically applicable material groups. The results make clear that awareness has to be raised regarding the materials used for the LCPC test. An abrasive can be classified differently just by using various materials of the same hardness. In order to obtain reliable and reproducible index values for the abrasiveness of crushed rock, it is necessary to consider the influence of materials in future recommendations for the LCPC. Die Abrasivität von Lockergestein wird im Rahmen der Planungsphase eines Tunnelbauprojekts zur Abschätzung des Verschleißes an Abbau‐ und Bohrwerkzeugen bestimmt, beispielsweise durch den LCPC‐Abrasivitätstest. Aus werkstofftechnischer Sicht ergeben sich Schwierigkeiten in Bezug auf die Aussagekraft eines solchen Indexwertes, da wichtige tribologische Einflussfaktoren wie z. B. das Gefüge des Prüfflügels (Größe, Phasenzusammensetzung) in der aktuellen Prüfnorm (AFNOR P18‐579) nicht berücksichtigt werden. Im Rahmen dieser Untersuchung wurden LCPC‐Versuche mit Drehflügeln aus verschiedenen Stählen gleicher und unterschiedlicher Härte gegen zwei Abrasive (Mohshärte 7, 9) durchgeführt, um den Einfluss des Gefüges und den damit verbundenen tribo‐mechanischen Eigenschaften der Prüfflügelwerkstoffe auf den LCPC‐Indexwert (ABR) zu ermitteln. Neben Werkstoffhärten, die nach Norm gefordert werden (60 bis 75 HRB ≈ 105 bis 140 HV 10 nach DIN EN ISO 18265‐2013), fanden auch Prüfwerkstoffe mit höheren Härtewerten Anwendung, um die Datenbasis des LCPC‐Abrasivitätsindex auf diese anwendungsnahen Werkstoffgruppen auszuweiten. Die Ergebnisse verdeutlichen, dass eine Sensibilisierung im Umgang mit dem LCPC‐Versuch in Bezug auf die verwendeten Werkstoffe erforderlich ist. Ein Abrasiv lässt sich unterschiedlich klassifizieren, nur durch die Nutzung von verschiedenen Werkstoffen derselben Härte. Um aussagekräftige und reproduzierbare Indexwerte für die Abrasivität von Lockergestein bestimmen zu können, ist es notwendig, werkstofftechnische Einflüsse in zukünftigen Empfehlungen für den LCPC‐Versuch zu berücksichtigen.